Pengaruh Jenis Stripping Agent Pada Fasa Internal Menggunakan Metode Emulsion Liquid Membrane Dalam Pemisahan Logam Pengompleks - Purba, Anita Zefanya Marchelina; H Bahti, Husen; P Fauzia, Retna; Pratomo, Uji; Wyantuti, Santhy (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2024)
Heavy metals have a high density, atomic weight, or atomic number. Heavy metals are potentially hazardous to health and the environment and must be separated. Emulsion liquid membrane is a promising technique to remove heavy metal contaminants from industrial and household effluents. Emulsion liquid membrane (ELM) is used to separate heavy metals as it is effective and efficient. ELM involves external, membrane, and internal phases. The internal phase is essential in the separation process as it carries stripping agents to pull metals from the membrane to the internal phase. The choice of stripping agent concentration in the internal phase, such as HNO3, H2SO4, HCl, NaOH, and Na2CO3, affects the extraction efficiency in separating heavying metals using ELM. This article evaluates the effect of stripping agent concentration on extraction efficiency.